BLASTOCYSTIS AND OTHER INTESTINAL PARASITES INFECTIONS IN ELEMENTARY SCHOOL CHILDREN IN DUKUH VILLAGE, KARANGASEM DISTRICT, BALI - Diarthini, Ni Luh Putu Eka; Swastika, I Kadek; Ariwati, Luh; Isyaputri, Rahmadany; Fitri N, Moh. Yasin; Hidajati, Sri; Basuki, Sukmawati (Indonesian Journal of Tropical and Infectious Disease, 2018)
Blastocystis spp. is the most common enteric parasitic infection found in several community surveys from developing countries. Blastocystis infections may cause gastrointestinal symptoms, but also cause extraintestinal symptoms such as urticaria and joint pain. Blastocystis infection can also be asymptomatic or a carrier. However, the prevalence of Blastocystis infection in children has not yet been fully investigated in Indonesia, particularly in Bali Province. This study aimed to determine the prevalence of Blastocystis and other intestinal parasites in elementary school children stools in Dukuh village, Karangasem regency. A cross sectional study was conducted in September 2016. A total of 103 school children stools were collected by informed consent and parasites were examined by microscopy with wet mounts method using Lugol's iodine solution. Thirty-five school children were infected with Blastocystis spp. (35/103, 34%) that consisted of a single infection (29/35, 82.9%) and mix infection with other parasites (6/35, 17.1%). The mix infections were Blastocystis spp. and hookworm infection (1/6, 16.7%), Blastocystis spp. and Entamoeba coli (1/6, 16.7%), Blastocystis spp. and Giardia lamblia (2/6, 33.3%), Blastocystis spp. and Entamoeba histolytica/ Entamoeba dispar (1/6, 16.7%) and Blastocystis spp. and Entamoeba histolytica/ Entamoeba dispar and Giardia lamblia (1/6, 16.7%). The vacuolar forms of Blastocystis were dominantly found, in which was non-infectious form, whereas the infectious form is the cyst form and Blastocystis density was observed less than 5 cells per field of view at 400 magnification in all cases. This study concluded that the high prevalence of Blastocystis infection in elementary school children in Dukuh Village, Karangasem District, Bali that were dominantly single infections and several mix infections with other intestinal parasites. The high prevalence of Blastocystis infection in elementary school children suggested that it needs proper prevention measures for the children in this study area.